O3 variability in the troposphere as observed by IASI over 2008–2016: Contribution of atmospheric chemistry and dynamics - Wespes, Catherine; Hurtmans, Daniel; Clerbaux, Cathy; Coheur, Pierre (2017)
We analyze the ozone (O3) variability in the troposphere (from ground to 300 hPa) using 8 years (January 2008 to March 2016) of O3 profile measurements provided by the Infrared Atmospheric Sounding Interferometer (IASI) on board the MetOp satellite. The capability of IASI to monitor the year-to-year variability in that layer is examined first in terms of vertical sensitivity, a priori contribution, and correlations in the deseasonalized anomalies with the upper layers. We present global patterns of the main geophysical drivers (e.g. solar flux, Quasi-biennal Oscillation—QBO, North Atlantic Oscillation—NAO, and El Niño–Southern Oscillation—ENSO) of IASI O3 variations, obtained by applying appropriate annual and seasonal multivariate regression models on time series of spatially gridded averaged O3. The results show that the models are able to explain most of the O3 variability captured by IASI. Large O3 changes in the North Arctic/Euro-Atlantic sector and over the equatorial band are attributed to the NAO and the QBO effects, respectively. ENSO is modeled as the main contributor to the O3 variations in the tropical band where direct effects of warm and cool ENSO phases are highlighted with a clear tropical-extratropical gradient. A strong west-east gradient in the tropics is also found and likely reflects an indirect effect related to ENSO dry conditions. Finally, we also show that the ENSO perturbs the O3 variability far from the tropics into middle and high latitudes where a significant 4-month time-lag in the response of O3 to ENSO is identified for the first time. SCOPUS: ar.j info:eu-repo/semantics/published